Peningkatan Kapasitas Wirausaha melalui Pelatihan Digital Marketing di Desa Glondonggede Tambakboyo, Tuban - Istiqomah, Nur Hidayatul; Supriyanto, Supriyanto; Cahyati, Yuni (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to increase entrepreneurial capacity in Glondonggede Village, Tambakboyo, by providing Digital Marketing training on August 25 2023. This village has great potential in the small business sector, but many entrepreneurs have not utilized digital marketing to its full potential. Therefore, this training was held to provide the skills and knowledge needed so that entrepreneurs can develop their businesses in the digital era. The implementation method used is a participatory and integrated approach, starting with an initial survey to determine participants' needs, followed by intensive training and discussion sessions to ensure in-depth understanding. The results of this activity show that participants succeeded in improving their skills in using digital platforms for marketing, which is expected to accelerate the growth of their businesses.